2021
DOI: 10.1177/0095798421997215
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Jezebel Stereotype Endorsement and Sexual Behaviors Among Black College Women

Abstract: Researchers suggest that the Jezebel stereotype exerts a significant influence on Black women’s sexual decision making. The current qualitative study drew upon narrative data from individual, semistructured interviews with 50 Black women (ages 18-24 years) to explore how the Jezebel stereotype influenced their sexual beliefs and behaviors. Using consensual qualitative research methods, the following four themes emerged from the data: (a) how the Jezebel plays a role in their sexual exploration, (b) how the Jez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Consistent with CRF (Wing, 2000), gendered racism was a medium through which purity culture "continually refashioned images in order to solicit support for the U.S. matrix of domination" (Collins, 2015, p. 284). The results of the present study align with existing literature on the gendered-racist Mammy/Jezebel dichotomy (Anderson et al, 2018;Collins, 2015;Leath et al, 2021;Thomas et al, 2008) and reveal how this trope, a byproduct of the enslavement era, perpetuates gendered racism through the purity culture socialization processes. Although WoC still contend with a myriad of manifestations of gendered racism, knowledge of these specific manifestations is pertinent to efforts to dismantle white supremacy within dominant institutions, such as that of Christianity and the purity movement.…”
Section: Modern Manifestations Of Cultural Imperialism and Gendered R...supporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with CRF (Wing, 2000), gendered racism was a medium through which purity culture "continually refashioned images in order to solicit support for the U.S. matrix of domination" (Collins, 2015, p. 284). The results of the present study align with existing literature on the gendered-racist Mammy/Jezebel dichotomy (Anderson et al, 2018;Collins, 2015;Leath et al, 2021;Thomas et al, 2008) and reveal how this trope, a byproduct of the enslavement era, perpetuates gendered racism through the purity culture socialization processes. Although WoC still contend with a myriad of manifestations of gendered racism, knowledge of these specific manifestations is pertinent to efforts to dismantle white supremacy within dominant institutions, such as that of Christianity and the purity movement.…”
Section: Modern Manifestations Of Cultural Imperialism and Gendered R...supporting
confidence: 90%
“…Given that gendered racist ideologies are the backbone of purity culture rhetoric and extant literature has examined the enduring harmful effects of racist tropes and stereotypes (Anderson et al, 2018; Collins, 2015; hooks, 1981; Leath et al, 2021), WoC’s experiences are crucial to understand the harm perpetuated by purity culture and the ways in which it upholds white supremacy and furthers the subjection of Black and Brown women. Although literature specific to purity culture has focused on white womanhood, there are Scholars of Color who discuss closely related constructs within the domain of religion that are adjacent to purity culture.…”
Section: Intersectional Erasure Of Women Of Color In Purity Culturementioning
confidence: 99%
“…Parents who occupy a minoritized social location or who have children who do might have different goals than parents in a social location with more privilege. For example, Black mothers preparing their daughters to deal with intersecting societal oppression from sexism and racism may tailor their PCSC to include protective messages to prevent them from acting out racialized sexual stereotypes (e.g., Jezebel) or being taken advantage of due to these stereotypes (Leath et al, 2020(Leath et al, , 2021. For parents of children with autism, the common fear of someone taking F I G U R E 1 An expanded theoretical perspective.…”
Section: Goalsmentioning
confidence: 99%
“…Those at greater risk for sexual and relationship violence are those in more oppressed social locations as well (Black et al, 2014;Montgomery et al, 2015;Peitzmeier et al, 2020;Walters et al, 2013). Further, innumerable harmful sexual racial stereotypes and expectations exist such as the Jezebel stereotype that hypersexualizes Black women (Leath et al, 2021), expectations of Mexican women to conform to traditional feminine gender roles (Moraga, 1983), stereotypes of Asian men being inadequate sexual or romantic partners (Wong et al, 2012), and stereotypes that men of color are more sexually violent than their White counterparts (Chouhy & Madero-Hernandez, 2019;Patton & Snyder-Yuly, 2007). Existing in a more minoritized social location and regularly experiencing discrimination and the effects of oppression in relation to sexuality will likely affect how someone parents and their beliefs and behaviors related to PCSC.…”
Section: Expanding the Sct Environmental Factor: Social Locationmentioning
confidence: 99%
“…For example, a study by Cody (2019) of 68 Black female graduate social work students found that nearly a quarter indicated frequently combating anti-Black stereotypes including, the "angry Black woman" or Sapphire trope (p. 88). Similarly, a recent qualitative study by Leath et al (2021) who analyzed the narratives of 50 Black women enrolled at two predominantly white universities, discovered that the Jezebel stereotype and threat of being associated with this enduring (trans)misogynoir trope, continues to inform the sexual behaviors and choices of Black women in college today. Another qualitative study by McGee and Kazembe (2016) examined the experiences and critiques of 33 Black faculty (14 women) while presenting their research at professional venues.…”
Section: Gendered Anti-blackness In Higher Educationmentioning
confidence: 99%